Claim trading as a misuse of law. Issue 1 (2nd January 2020) - Matějková, Ing. Jitka; Pavelek, Bc. Ondřej
Abstract : The aim of this paper is to discuss and answer the issue whether the trading of claims and their use in civil proceedings may be an abuse of rights. Claims processing is a regular part of the business both in the Czech Republic and within the European Union. The European Commission proposed a special regulation governing the applicable law in 2018, as well emphasizes the legal arrangements for the assignment, especially its assets. Claims are made both between large business corporations and small business owners. Assignment of claims is also very important in ensuring the liquidity of a particular entrepreneur. If the assignment of a claim is made in the course of civil proceedings, the plaintiff – the promoter – usually submits a proposal for a procedural succession for bringing the assignee in the proceedings in their place. However, this right is easily abuse-able if it is an entrepreneur of a business corporation that fights with financial difficulties. In case of dismissal the defendant will not be entitled to reimbursement of the costs.